2022
DOI: 10.31098/ijebce.v2i1.722
|View full text |Cite
|
Sign up to set email alerts
|

Bank’s Digitalization and Financial Performance during Pandemic in Indonesia

Abstract: The pandemic-led recession has made a downturn in the banking industry’s performance. Digitalization is seen as a good strategy to support banks' business operations during the pandemic-led recession. This paper focus on how the banking and financial industry maintained their performance during the covid-19 led recessions through digitalization. I use descriptive statistics approach and regression analysis to analyze how digital transformation help to maintain business performance during a pandemic. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
0
5
0
2
Order By: Relevance
“…Further, Papadopoulos et al (2020) and Mariani and Borghi (2020) argue that digitalization has enabled small-scale firms to respond effectively to the crisis by making use of their dynamic capabilities and financial inclusion. However, the pandemic-led recession period revealed that digital transactions have helped the banking industry to maintain its profit, even though pandemics have to some extent had negative impacts on banks' performance (Khairina, 2022;Lu et al, 2022).…”
Section: Digitalization Of Corporate Financementioning
confidence: 99%
“…Further, Papadopoulos et al (2020) and Mariani and Borghi (2020) argue that digitalization has enabled small-scale firms to respond effectively to the crisis by making use of their dynamic capabilities and financial inclusion. However, the pandemic-led recession period revealed that digital transactions have helped the banking industry to maintain its profit, even though pandemics have to some extent had negative impacts on banks' performance (Khairina, 2022;Lu et al, 2022).…”
Section: Digitalization Of Corporate Financementioning
confidence: 99%
“…Based on previous research, digital banking adoption or IT investment positively impacts performance (Kahveci & Wolfs, 2018;Mbama et al, 2018;Wirdiyanti, 2018). Digital banking adoption also effects bank operation and efficiency (Azmi et al, 2020;Islam et al, 2019;Jünger & Mietzner, 2020;Khairina, 2022;Malar et al, 2019;Son et al, 2020;Wadesango, 2020;Wirdiyanti, 2018). However, several researchers believe that digital adoption in the banking industry positively affects the bank's performance.…”
Section: Digital Banking Adoption and Performancementioning
confidence: 99%
“…The advancement of information and communication technology in the modern era has brought significant changes in various aspects of life, including the financial sector (Khairina, 2022). This technology has enabled people to engage in digital transactions and payments more easily and efficiently.…”
Section: Introductionmentioning
confidence: 99%